Penerapan Sistem Pengendalian Internal Perbankan Dalam Menunjang Efektivitas Pemberian Pembiayaan - Datiani Setia Ningsih (Faculty of Islamic Religion, Universitas Muhammadiyah Sumatera Utara, 2019)
This study aims to find out how the system of providing financing for small and medium enterprises, and to find out the internal banking control system that is applied in supporting the effectiveness of providing small and medium business financing at PT. Bank BNI Syariah Medan Branch Office.The method used in this study is descriptive qualitative method that is data obtained based on the results of research, then processed, analyzed and interpreted using existing theories to then draw conclusions.Based on the results of the study, the author draws the conclusion that the system of financing is applied to PT. Bank BNI Syariah Medan Branch Office the process is not too difficult and quite easy. And the application of an internal control system at PT. Bank BNI Syariah Medan Branch Office complies with COSO theory so that it can support the effectiveness of financing.